Effect of ohmic serial resistance on the efficiency of dye-sensitized solar cells - Dao, Van-Duong; Choi, Ho-Suk; Jung, Kwang-Deog (ELSEVIER, 2013)
A new counter electrode, which was simply fabricated with enlarging Pt-sputtered area, showed the energy conversion efficiency of 8.66 (+/- 0.06)%, which was higher than the 8.12(+/- 0.10)% efficiency of the conventional Pt-sputtered counter electrode. A decrease in ohmic internal resistance was also observed though EIS measurement. And the new counter electrode combined with the Pt hollow spheres electrode gave the energy conversion efficiency of 9.83(+/- 0.14)%. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: COUNTER-ELECTRODE; INTERNAL RESISTANCE; LOW-COST